Analisis Pertimbangan Hukum Kekerasan Dalam Rumah Tangga Sebagai Faktor Penyebab Perceraian (Studi Putusan Pengadilan Agama Manna Kelas II No. 0018/Pdt.G/2014/PA.Mna dan No. 0466/Pdt.G/2014/PA.Mna) - Iwanto, Iwanto (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2016)
Abstract: Analysis Of Legal Considerations On Household Violence As A Factor Causes Of Divorce (Case Study Of Religious Courts Verdict In Manna Class II No. 0018/Pdt.G/2014/PA.Mna dan No. 0466/Pdt.G/2014/PA.Mna). Based on reports of the National Commission for Women gathered from Religious Court, it shows that the Religious Court is the first door to reveal the household violence. This study will address whether the acts of household violence may be a reason to file for divorce? And what is to be considered by Manna Religious Court in deciding a divorce case by reason of household violence? This research is a qualitative juridical normative approach to legislation and case study approach. The result shows thathousehold violence can be used as an excuse to initiate divorce (Law No. 23 Year 2004 concerning the Elimination of Household Violence Article 5, 44, 45). It can be linked to the Marriage Act jo Government Regulation No. 9 of 1975, and the Compilation of Islamic Law (Presidential Decree No. 1 of 1991 Section 19 (b) and (d) of Government Regulation No. 9 of 1975 and Section 116 (b). Manna Religious Court in deciding a divorce case by reason of household violence, namely the decision number: 0018 / Pdt.G / 2014 / PA.Mna, the contested divorce, the legal basis for its consideration, namely, Article 39 paragraph (2) of law No. 1 Year 1974 Jo. Section 116 (g) Compilation of Islamic law. Accordingly, the plaintiff had been grounded and is not against the law. However, the decision in its consideration of the judges did not mention about the mediation process.